A hand hygiene intervention to reduce infections in child daycare: a randomized controlled trial - ZOMER, T. P. (Epidemiol Infect, 2015)
Infections are common in children attending daycare centres (DCCs). We evaluated the effect of a hand hygiene (HH) intervention for caregivers on the incidence of gastrointestinal and respiratory infections in children. The intervention was evaluated in a two-arm cluster randomized controlled trial. Thirty-six DCCs received the intervention including HH products, training sessions, and posters/stickers. Thirty-five control DCCs continued usual practice. Incidence of episodes of diarrhoea and the common cold in children was monitored by parents during 6 months. Using multilevel Poisson regression, incidence rate ratios (IRRs) with 95% confidence intervals (CIs) were obtained. Diarrhoeal incidence was monitored in 545 children for 91 937 days. During follow-up, the incidence was 3·0 episodes per child-year in intervention DCCs vs. 3·4 in control DCCs (IRR 0·90, 95% CI 0·73–1·11). Incidence of the common cold was monitored in 541 children for 91 373 days. During follow-up, the incidence was 8·2 episodes per child-year in intervention DCCs vs. 7·4 in control DCCs (IRR 1·07, 95% CI 0·97–1·19). In this study, no evidence for an effect of the intervention was demonstrated on the incidence of episodes of diarrhoea and the common cold.